(untitled) (NAU Journal of Library and Information Science, 2019)
Resource Description and Access is a content standard that was recently developed by the library community to harness the advantages of the semantic web by supporting the creation of robust cataloguing data capable of integrating with other information repositories. Many countries from the developed world have deployed this code in their cataloguing process. Some countries in Africa have also started using RDA. This study investigated the preparedness of academic libraries in Southeast Nigeria for the implementation of RDA. Descriptive survey research method was employed and data was collected through questionnaire from twenty-one cataloguers in eleven academic libraries. Data collected was analysed using simple percentage. Result from the analysis show that academic libraries from Southeast Nigeria are not yet prepared to implement the RDA rules. Technological infrastructure is inadequate in these libraries whereas training for RDA implementation is almost non-existent. The study recommends that library schools should update their curriculum to include training in the use of RDA rules while the National Library of Nigeria and the Nigerian Library Association should play a lead role in the implementation of RDA.